Achieving high strength-ductility synergy in Mg-6Sn-3Zn-0.3Zr (wt.%) alloy via a combination of casting, pre-treatment and hot extrusion - Tianshui Zhou; Yaqin Li; Feifei Guo; Qinglin Li; Zhi Jia; Dexue Liu (Journal of Magnesium and Alloys)
Achieving the strength-ductility synergy in Mg alloys is a gigantic challenge, especially in rare-earth-free Mg alloys. In this study, a new Mg-Sn-Zn-Zr alloy with high ultimate tensile strength (∼284–326 MPa) without sacrificing elongation-to-failure (∼22.1–27.6%) was developed by utilizing casting, pre-treatment and hot extrusion. Strong random rather than basal texture is observed both in as-cast and pre-treatment samples. Subsequently, the strong texture is effectively weakened via hot extrusion whilst remaining random. More importantly, after hot extrusion, the grain sizes of as-cast and pre-treatment samples were significantly refined down to about 10 µm. Examination of as-extruded microstructures of the alloy reveals that the grain refinement is highly associated with the particle stimulated nucleation (PSN) and continuous/discontinuous dynamic recrystallization (C/DDRX) mechanisms. Moreover, the results suggest that the combination of pre-treatment and hot extrusion not only promotes multiplication of geometrically-necessary dislocations (GNDs) but enhances dynamic precipitation, which boosts the formation of fine and homogenous precipitates. Based on the results of X-ray diffraction (XRD), transmission electron microscope (TEM) and selected area electron diffraction (SAED), the precipitates are Mg2Sn phases. Furthermore, the main orientation relationship identified by high resolution TEM (HRTEM) between Mg2Sn phases and α-Mg matrix could be described as (111)Mg2Sn or (220)Mg2Sn ∥ (0001)Mg with a coherent interface. The refined grains size, ultra-fine precipitates and high density of GNDs would substantially contribute to the enhancement of the strength and the corresponding contributions are calculated to be ∼183–185 MPa, ∼30.9–38 MPa and ∼14.2–31.7 MPa, respectively. Besides, texture weakening or randomizing, grain refinement and coherent interfaces are mainly responsible for the high ductility. The current study can provide beneficial insights into the development of high-performance rare-earth-free Mg alloys with favorable microstructure via a combination of casting, pre-treatment and hot extrusion processing.